2017
DOI: 10.1111/acem.13246
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Advanced Cardiac Life Support for Out‐of‐hospital Cardiac Arrest: A Cohort Study

Abstract: In a tiered-response urban emergency medical service setting, prehospital ACLS is not associated with an improvement in survival to hospital discharge in patients suffering from OHCA and in potential E-CPR candidates, but with an improvement in prehospital ROSC and with longer delay to hospital arrival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
11
2
Order By: Relevance
“…The methods used to collect and extract the data for the initial registry have been described previously. 3,18,21 Patient data are entered by the paramedic on a "run-sheet" following every call. Patients suffering from an OHCA are identified using these run-sheets.…”
Section: Methods and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods used to collect and extract the data for the initial registry have been described previously. 3,18,21 Patient data are entered by the paramedic on a "run-sheet" following every call. Patients suffering from an OHCA are identified using these run-sheets.…”
Section: Methods and Measurementsmentioning
confidence: 99%
“…1,2 Rates of survival for these patients remain low, with only 5% to 10% of all OHCA surviving to hospital discharge. 1,3,4 However, patients with an initial shockable rhythm, such as ventricular fibrillation and pulseless ventricular tachycardia, have a better prognosis than patients whose initial rhythm is non-shockable (pulseless electrical activity or asystole). 3,[5][6][7] This may be explained by shockable rhythms being a marker of earlier intervention (i.e., prior to deterioration to asystole) or simply that the single best available therapy for patients suffering from a cardiac arrest (defibrillation) is only effective in patients with these rhythms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, obtaining oh-ROSC through advanced cardiac life support is itself not associated with an improvement in the survival to hospital discharge in patients with CPA, so achieving a balance between obtaining oh-ROSC over time and early transportation to perform aggressive medical treatment in hospital may be important for treating patients with CPA in the prehospital setting. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies revealed that prehospital advanced life support (ALS) was not effective for OHCA patients (6)(7)(8)(9)(10). The experience of the paramedics exposed to the OHCA patients affects the treatment of cardiac arrest; however, the actual exposure of the paramedics is rare and declining.…”
Section: Introductionmentioning
confidence: 99%